PENGARUH RASIO FUNDAMENTAL TERHADAP NILAI PERUSAHAAN DENGAN HARGA SAHAM SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN SUBSEKTOR BATUBARA YANG TERDAPAT DI BEI TAHUN 2017 - 2019 - Syahzuni, Barlia Annis (Lembaga Penerbitan Unversitas Esa Unggul, 2021)
This research aims to determine empirically the effect of the company's fundamental ratio which in this study is proxied by return on equity (ROE), current ratio (CR), and debt to equity ratio (DER) on the value of the company which is measured using price earning ratio (PER) and also to see whether stock prices affect this relationship. The coal sub-sector companies listed on the Indonesia Stock Exchange for the period 2017 - 2019 are the population chosen in this study. Sampling was done by purposive sampling, obtained 11 companies in the study period that met the data collection criteria, so that the total financial reports collected were 33 audited financial reports. The type of data is secondary data obtained from the official website www.idx.co.id. The analysis method used is multiple regression analysis. The results shown in this study are partially ROE has a positive effect and DER has a negative effect on stock prices, while CR has no effect on stock prices. Simultaneously, the three fundamental ratios have a significant effect on stock prices. Either partially or simultaneously ROE, CR, and DER have no effect on firm value. This study shows that stock prices have a significant effect on firm value, but stock prices are not an intervening variable in seeing the relationship between fundamental ratios and firm value. Keywords: Fundamental ratio, stock price, firm value